Increased gastric juice leukotriene B₄, C₄ and E₄ concentrations in children with Helicobacter pylori colonization - Kasırga, Erhun; Çoker, Isıl; Aydoğdu, Sema; Yağcı, Raşit V.; Taneli, Baha; Gousseinov, Afig (The Turkish Journal of Pediatrics, 1999)
During recent years, the role of inflammatory lipid mediators in the pathophysiology of Helicobacter pylori (H. pylori) infections has been investigated in several studies. The concentrations of leukotrienes (LTs) in gastric juice from H. pylori positive (n = 13) and negative (n = 18) children with recurrent abdominal pain were studies in order to determine whether these lipid inflammatory mediators are involved in local and systemic biological actions. Gastric juice samples and biopsy specimens of mucosa were obtained endoscopically from 31 patients with recurrent abdominal pain for assessment of LTs and histopathological examination. In this study, all children with recurrent abdominal pain were investigated by rapid urease test and histological assessment for H. pylori colonization. Leukotriene levels were measured by high performance liquid chromatography (HPLC) and radioimmunoassay (RIA) in gastric juice samples. Gastric juice LTB₄, LTC₄, and LTE₄ levels were significantly higher in patients with H. pylori colonization than in children without H. pylori colonization. These results indicate that increased gastric content of proinflammatory mediators (LTB₄, LTC₄, and LTE₄) may be related to the pathogenesis of H. pylori-associated gastritis.
Keywords: Helicobacter pylori; antral gastritis; leukotrienes; lipid mediators; gastric juice